2017
DOI: 10.1186/s13065-017-0324-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of phenolics and flavonoids extraction conditions of Curcuma Zedoaria leaves using response surface methodology

Abstract: This study focused on maximizing the extraction yield of total phenolics and flavonoids from Curcuma Zedoaria leaves as a function of time (80–120 min), temperature (60–80 °C) and ethanol concentration (70–90 v/v%). The data were subjected to response surface methodology (RSM) and the results showed that the polynomial equations for all models were significant, did not show lack of fit, and presented adjusted determination coefficients (R2) above 99%, proving their suitability for prediction purposes. Using de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 24 publications
5
39
0
6
Order By: Relevance
“…According to previous findings, TPC and TFC of (85.64 ± 0.52) mg GAE g DW −1 and (52.72 ± 0.93) mg QE g DW −1 , respectively, were obtained from Vernonia cinerea leaves under MAE conditions of an irradiation time of 2 min, an ethanol concentration of 47 % (v/v), a feed/solvent of 1:14 (g mL −1 ), and a microwave power of 444 W . Moreover, extraction of Curcuma zedoaria leaves resulted in TPC of (125.75 ± 0.17) mg GAE per gram of extract and TFC of (6.12 ± 0.23) mg QE per gram of extract under optimal conditions of an extraction temperature of 75 °C, an extraction time of 92 min, and an ethanol concentration of 90 % (v/v) .…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…According to previous findings, TPC and TFC of (85.64 ± 0.52) mg GAE g DW −1 and (52.72 ± 0.93) mg QE g DW −1 , respectively, were obtained from Vernonia cinerea leaves under MAE conditions of an irradiation time of 2 min, an ethanol concentration of 47 % (v/v), a feed/solvent of 1:14 (g mL −1 ), and a microwave power of 444 W . Moreover, extraction of Curcuma zedoaria leaves resulted in TPC of (125.75 ± 0.17) mg GAE per gram of extract and TFC of (6.12 ± 0.23) mg QE per gram of extract under optimal conditions of an extraction temperature of 75 °C, an extraction time of 92 min, and an ethanol concentration of 90 % (v/v) .…”
Section: Resultssupporting
confidence: 53%
“…The optimal recovery of TPC might be due to the polarity of the solvent used in extraction. A previous report showed that ethanol and water were environmentally friendly solvents that could extract a higher quantity of phenolic compounds from the plant matrix . In a similar study, Dahmoune et al obtained a TPC of (162.49 ± 16.95) mg GAE g DW −1 from Myrtus communis leaves under MAE optimal conditions of 42 % (v/v) ethanol concentration, irradiation time of 62 s, microwave power of 500 W, and solvent‐to‐material ratio of 32 (mL g −1 ) .…”
Section: Resultsmentioning
confidence: 89%
“…The diffusion increases not only because of the increase of the extraction temperature but also due to improved hydrodynamic conditions [44]. Namely, the viscosity of the solvent decreases with increasing the temperature, which increases the penetration rate in the plant material, and consequently the concentration of flavonoids in the extract [45].…”
Section: (1) (2019) 10-18mentioning
confidence: 99%
“…Besides that, the high temperature can reduce the thermal resistant of a targeted cell in natural material. In a study by Azahar. (2017) show that the range of targeted compound groups such as flavonoid and phenolic were between 60 ºC to 80 ºC [15].…”
Section: B Response Surface Analysis Of Bcbmentioning
confidence: 99%
“…In a study by Azahar. (2017) show that the range of targeted compound groups such as flavonoid and phenolic were between 60 ºC to 80 ºC [15]. This in agreement with Guangyan et al 2012found the same range to extract the bioactive compound from natural material [16].…”
Section: B Response Surface Analysis Of Bcbmentioning
confidence: 99%